Normalization Procedures of Borrowings in Uzbek Language - Kurbonov, Abdulhamid; Darvishov , Ibrohim; Kuziev, Umidjon (International Journal of Psychosocial Rehabilitation, 2020)
This article describes borrowing words in the Uzbek language, their classification, and aspects of study, factors of activation of borrowings and their expression in the explanatory dictionaries of the Uzbek language.